THE PREDICTOR FACTORS OF OBESITY RISK IN RURAL ADULTS IN CIHANJUANG RAHAYU VILLAGE - Elon, Yunus; Malinti, Evelin; Simanjuntak, Samuel Maju; Pasongli, Yunita (Journal of Islamic Nursing, 2021)
Obesity known as risk factor of non-communicable diseases such as; heart disease, hypertension, stroke, diabetes mellitus, and cancer. These diseases has become the top cause of death both globally and nationally. This study aims to investigate the relationship between demographic factors and the risk of obesity. This study utilized a quantitative method with a descriptive correlation approach. The subjects of the study were the Cihanjuang Rahayu villagers aged 26-45 year old who were selected by accidental sampling technique. A total of 150 subjects signed the informed concent to participate in this study. The data analysis using chi-square test showed a significant relationship between gender, age, occupation, marriage status and BMI (p<0.05). There is no significant relationship between income and BMI (p>0.5). Being female, married, middle age, and work as housewife are more likely to be obese. So people with these characteristic are encouraged to maintain BMI in normal range. Future research could examine other factors that have an effect on BMI such as nutritional intake.